Book Review: Public Policymaking: An Introduction - KUREBWA, Jeffrey; Mhaka Martin Chirume,; Kuwanda Farai, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The book is interested in categories of public policy formulation in America. There are number of policies at play and being used at once and this book put them in groups or sets for easy reference. Public policies are a bit complex (not easy to understand) to understand policies there is need for legislative mind to be at play. This book summarises the policies making them simple to understand. Their applicability becomes easier.Insights of public policies formulated at national, state and local government are also considered. The policies formulated at different level of governance and their purpose or what they serve is highlighted. This helps in understanding further the policies. So the development of public policies according to this book is done at national, state and local level. The nature of the problem determines the policy and the policy makers.In a two term congress in America at least 300-400 laws are enacted. Why these laws are enacted is also explained in this book. The assumption is that a new president will come with his /her own vision where improvements are needed according to the party ideology and this will normally necessitate the formulation of new laws or development, modification or amendments of the existing policy. These policies deal with public housing, higher education, internal revenue service reform, etc. Comparing this with Zimbabwean scenario it is quite interesting to note that policy formulation or amendments to address issues such as higher education where for example the former minister of higher education advocates for the education system to move towards science. He embraced science as the way to go, and the current minister is completely focussing on something else. On public housing the Zimbabwean authorities came up with a housing policy which is always modified and have a code name ready for a purpose whenever there is an opportunity. It used to be code named ‘House for all’ to ‘operation hlalani kuhle’ on revenue of late there are quite a number of policies being introduced such as the unpopular 2% on every electronic transaction.